The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41438-021-00667-z
|View full text |Cite
|
Sign up to set email alerts
|

The MdABI5 transcription factor interacts with the MdNRT1.5/MdNPF7.3 promoter to fine-tune nitrate transport from roots to shoots in apple

Abstract: Nitrate is a major nitrogen resource for plant growth and development and acts as both a crucial nutrient and a signaling molecule for plants; hence, understanding nitrate signaling is important for crop production. Abscisic acid (ABA) has been demonstrated to be involved in nitrate signaling, but the underlying mechanism is largely unknown in apple. In this study, we found that exogenous ABA inhibited the transport of nitrate from roots to shoots in apple, and the transcription of the nitrate transporter MdNR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…For example, in a very recent study, two bZIP TFs, including bZIP29 and Opaque2, were phosphorylated by SnRK2.2 to transactivate downstream target genes for endosperm filling in maize (Yang et al, 2022). In addition, either SnRK2s or ABFs have been separately shown to act as the pivotal regulators of various physiological and biological processes, such as root growth (Liu et al, 2021), stomatal development (Ding et al, 2020), sugar metabolism (Ma et al, 2017a), flower senescence (J. Z.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a very recent study, two bZIP TFs, including bZIP29 and Opaque2, were phosphorylated by SnRK2.2 to transactivate downstream target genes for endosperm filling in maize (Yang et al, 2022). In addition, either SnRK2s or ABFs have been separately shown to act as the pivotal regulators of various physiological and biological processes, such as root growth (Liu et al, 2021), stomatal development (Ding et al, 2020), sugar metabolism (Ma et al, 2017a), flower senescence (J. Z.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a very recent study, two bZIP TFs, including bZIP29 and Opaque2, were phosphorylated by SnRK2.2 to transactivate downstream target genes for endosperm filling in maize (Yang et al ., 2022). In addition, either SnRK2s or ABFs have been separately shown to act as the pivotal regulators of various physiological and biological processes, such as root growth (Liu et al ., 2021), stomatal development (Ding et al ., 2020), sugar metabolism (Ma et al ., 2017a), flower senescence (J. Liu et al ., 2017; Z. Liu et al ., 2017), and abiotic stress response (Chen et al ., 2020; Takahashi et al ., 2020; Li et al ., 2021), among others. As increasing evidence showed that activation of ABFs requires SnRK2‐mediated phosphorylation (Kobayashi et al ., 2005; Wang et al ., 2012; Umezawa et al ., 2013; W. Wang et al ., 2019; X. Wang et al ., 2019), it is reasonable to assume that SnRK2s and ABFs in various combinations might function in synergy to play crucial roles in the regulation of plant development and responses to environmental stresses.…”
Section: Introductionmentioning
confidence: 99%
“…AtNRT2.7 is induced by nitrate and hormones, enhances the growth of the root system, and improves the absorption and utilization of nitrogen [ 47 ]. In apples, the expression of MdNRT1.5 / MdNPF7.3 inhibits the transport of nitrate from root to branch [ 48 ]. Nitrate has been reported to mediate phosphorus absorption and starvation signals by activating the NIGT1-SPX-PHR cascade signaling pathway [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The apple calli was transiently transformed by Agrobacterium carrying ProMdERF113::GUS as previously described (Hu et al, 2017; Y. J. Liu et al, 2021). They were cultured on a solid medium containing NaCl (120 mM), PEG 6000 (4%), temperature (4°C), and ABA (100 μM) for 24 h, respectively.…”
Section: Methodsmentioning
confidence: 99%